2006
DOI: 10.1111/j.1600-0404.2005.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the determinants of 1-year post-stroke outcomes in elderly patients

Abstract: Predictive models--by developing new strategies to improve outcomes through identifying treatable predictive factors--may be clinically useful in elderly stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 19 publications
3
22
0
3
Order By: Relevance
“…13,21 Among studies not designed to examine sex differences, 5 reported that females had worse outcome than males in unadjusted analyses 10 and independent of age, 11,16,23,24 stroke severity, 23,24 prestroke disability, 23 comorbidities, 24 depression, 11 living alone, 11 recurrent stroke, 11 and cognitive impairments. 11 In contrast, others reported no association between sex and long-term functional outcomes in unadjusted analyses 11,12,20 or after adjusting for age, 16,18,[25][26][27][28][29][30][31] socioeconomic factors, 29 stroke severity, 17,18,25-27,29 -31 prestroke disability, 16,25,27 treatment, 27 mood, 18 and comorbidities. 15,17,26,29 There were fewer examinations of instrumental ADL by sex.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…13,21 Among studies not designed to examine sex differences, 5 reported that females had worse outcome than males in unadjusted analyses 10 and independent of age, 11,16,23,24 stroke severity, 23,24 prestroke disability, 23 comorbidities, 24 depression, 11 living alone, 11 recurrent stroke, 11 and cognitive impairments. 11 In contrast, others reported no association between sex and long-term functional outcomes in unadjusted analyses 11,12,20 or after adjusting for age, 16,18,[25][26][27][28][29][30][31] socioeconomic factors, 29 stroke severity, 17,18,25-27,29 -31 prestroke disability, 16,25,27 treatment, 27 mood, 18 and comorbidities. 15,17,26,29 There were fewer examinations of instrumental ADL by sex.…”
Section: Resultsmentioning
confidence: 94%
“…31 Our synthesis of the literature thus suggests that females have worse functional outcomes in the long term after stroke, but the difference between the sexes is greatly reduced when confounding factors are taken into account. Of the 12 studies that adjusted for at least age and stroke severity, 15,17,18,[21][22][23][24][25][26][27]29,30 4 reported that females had worse outcomes than males, whereas the remainder reported no sex difference. Important covariates appeared to be age, stroke severity, and prestroke functional status.…”
Section: Resultsmentioning
confidence: 99%
“…Afazija, kaip žymus pažintinių funkcijos sutrikimas, taip pat turi įtakos pacientų, persirgusių insultu, funkcinės būklės atsigavimui ir blogesnei ligos baigčiai (4,46,50). J. Y. M. Wee ir kiti autoriai nurodo, kad afazija ir kiti pažinimo sutrikimai koreliuoja su mažesnėmis FNT reikšmėmis išrašant pacientą po stacionarinės reabilitacijos (46).…”
Section: įVadasunclassified
“…Kiti autoriai nerado skirtumo tarp funkcinės būklės atsigavimo ir insulto pobūdžio (8,50). K. H. Sze ir kiti tyrė veiksnius, galinčius turėti įtakos pacientų, persirgusių insultu, funkcinės būklės atsigavimui po reabilitacijos.…”
Section: Insulto Pobūdis Lokalizacija Apimtisunclassified
See 1 more Smart Citation